2020
DOI: 10.3390/insects11090555
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Ecology of European Foul Brood Disease in the Honey Bee (Apis mellifera): Towards a Microbiome Understanding of Disease Susceptibility

Abstract: European honey bees (Apis mellifera Linnaeus) are beneficial insects that provide essential pollination services for agriculture and ecosystems worldwide. Modern commercial beekeeping is plagued by a variety of pathogenic and environmental stressors often confounding attempts to understand colony loss. European foulbrood (EFB) is considered a larval-specific disease whose causative agent, Melissococcus plutonius, has received limited attention due to methodological challenges in the field and laboratory. Here,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
46
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(47 citation statements)
references
References 64 publications
0
46
0
Order By: Relevance
“…Additionally, for one of their major experiments, Kešnerová et al (2019) [ 36 ] pooled 20 guts for each phenotype, whereas we examined individuals. Several recent studies indicate that when dysbiotic, the individual gut microbiome can increase substantially in size [ 34 , 35 ], such that a single dysbiotic individual could dominate the sampling results among 20 healthy individuals. Lastly, the microbiomes detailed by Kešnerová (2019) [ 36 ] may represent a recurrent enterotype because the non-winter seasons are dominated by Gilliamella with lesser amounts of Lactobacillus firm5 [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, for one of their major experiments, Kešnerová et al (2019) [ 36 ] pooled 20 guts for each phenotype, whereas we examined individuals. Several recent studies indicate that when dysbiotic, the individual gut microbiome can increase substantially in size [ 34 , 35 ], such that a single dysbiotic individual could dominate the sampling results among 20 healthy individuals. Lastly, the microbiomes detailed by Kešnerová (2019) [ 36 ] may represent a recurrent enterotype because the non-winter seasons are dominated by Gilliamella with lesser amounts of Lactobacillus firm5 [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, the microbiomes detailed by Kešnerová (2019) [ 36 ] may represent a recurrent enterotype because the non-winter seasons are dominated by Gilliamella with lesser amounts of Lactobacillus firm5 [ 27 ]. Most nurse/forager honeybee hindgut microbiomes sampled from non-winter are dominated by Lactobacillus firm5 [ 20 , 21 , 22 , 23 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ]. Although both hindgut enterotypes are potentially healthy, they may react differently to perturbation or seasonal changes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the recent 16S rRNA gene amplicon sequencing for investigating microbiota in honey, Lactobacillus kunkeei ( Apilactobacillus kunkeei ), Parasacharribacter apium ( Bombella apis ), Fructobacillus fructosus , Gilliamella apicola , Xanthomonadales and Actinomycetales were detected as major bacterial species/groups at the DNA level ( Floyd et al, 2020 ). Other previous studies reported that aerobic spore-forming bacteria of the genera Paenibacillus and Bacillus are commonly found in honey ( Snowdon and Cliver, 1996 ; Alippi et al, 2004 ; López and Alippi, 2007 ; López et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…OTC-resistant phenotypes observed in P. larvae develop, at least in part, due to plasmids carrying the tetracycline resistance gene [ tet (L)], and the plasmids may be transferable across bacterial species ( Murray and Aronstein, 2006 ; Alippi et al, 2007 , 2014 ; Murray et al, 2007 ). In honey, many bacteria, including Bacillus and Paenibacillus species, are known to exist ( Snowdon and Cliver, 1996 ; Alippi et al, 2004 ; Sinacori et al, 2014 ; Floyd et al, 2020 ). In a previous study, López et al (2008) isolated Bacillus cereus strains carrying a variety of tetracycline and OTC resistance genes, including tet (L) and tet (K), from honey, and suggested that bacteria in honey are a reservoir for tetracycline resistance genes.…”
Section: Introductionmentioning
confidence: 99%